2021
DOI: 10.1016/j.heliyon.2021.e07929
|View full text |Cite
|
Sign up to set email alerts
|

The andragogical value of content knowledge method: the case of an adult education programme in Kwa-Zulu Natal Province of South Africa

Abstract: The South African government has made a significant progress in the area of policy development and practice for Adult Education since independence in 1994. Still, there has been a tremendous increase in the number of adults without education. For example, KwaZulu-Natal, one of the provinces in South Africa, still recorded an increased number of illiteracy rate among adults, which further causes poverty and unemployment. The focus of this study is to explore the extend concept and ideas of andragogy are used by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…On the basis of continuity, it was possible to build a unified model of education, which includes vocational training, general cultural development and civic education. The study distinguishes a practical, systematic approach to improving anragogical education instead of an approach through the theoretical lens of andragogical theory (Akintolu & Letseka, 2021). The debatable aspect is the synergetic effect of adragogical and dual education, as in the study by Bashynska et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of continuity, it was possible to build a unified model of education, which includes vocational training, general cultural development and civic education. The study distinguishes a practical, systematic approach to improving anragogical education instead of an approach through the theoretical lens of andragogical theory (Akintolu & Letseka, 2021). The debatable aspect is the synergetic effect of adragogical and dual education, as in the study by Bashynska et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the theory of andragogy emphasizes the role of adult facilitators as someone whose major role is to guide the teaching and learning process, not as the transmittal of knowledge. Hence, facilitators are in charge of coordinating the learning process and facilitating the acquisition of content by the learners (Akintolu & Letseka, 2021). This study found the theory of andragogy very relevant because the theory indicates that the sole responsibility of literacy facilitators is to guide learning by identifying ways instruction and curriculum could be based on real-world or authentic situations familiar to the learners.…”
Section: Theoretical Frameworkmentioning
confidence: 92%
“…The implications for the practice of the andragogy assumptions especially for literacy facilitators and organisers to ensure a cooperative climate for learning, understand learner's specific needs and interests from which learning objectives must be developed, learning activities must be designed sequentially and learners' involvement in the selection of materials and resources as well as methods of instruction must be made a key component (Esra, 2011). These will help create a captivating learning environment that will suit the peculiar needs of adult learners and integrate their lives and careers (Akintolu & Letseka, 2021). Specifically, the theory of andragogy emphasizes the role of adult facilitators as someone whose major role is to guide the teaching and learning process, not as the transmittal of knowledge.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Knowles believes that adult learning must be done independently. Instead of being teacher-centered, adult learning should be student-centered and teach them the power of self-motivated learning (Akintolu & Letseka, 2021).…”
Section: Self Concept Implementationmentioning
confidence: 99%